Solvent-free microwave-assisted peroxidative oxidation of alcohols catalyzed by Iron(III)-TEMPO catalytic systems - Karmakar, Anirban (2016)
The iron(III) complexes [H(EtOH)][FeCl2(L)(2)] (1), [H(2)bipy](1/2)[FeCl2(L)(2)].DMF (2) and [FeCl2(L)(2,2'-bipy)] (3) (L = 3-amino-2-pyrazinecarboxylate; H(2)bipy = doubly protonated 4,4'-bipyridine; 2,2'-bipy = 2,2'-bipyridine, DMF = dimethylformamide) have been synthesized and fully characterized by IR, elemental and single-crystal X-ray diffraction analyses, as well as by electrochemical methods. Complexes 1 and 2 have similar mononuclear structures containing different guest molecules (protonated ethanol for 1 and doubly protonated 4,4'-bipyridine for 2) in their lattices, whereas the complex 3 has one 3-amino-2-pyrazinecarboxylate and a 2,2'-bipyridine ligand. They show a high catalytic activity for the low power (10 W) solvent-free microwave assisted peroxidative oxidation of 1-phenylethanol, leading, in the presence of TEMPO, to quantitative yields of acetophenone [TOFs up to 8.1 x 10(3) h(-1), (3)] after 1 h. Moreover, the catalysts are of easy recovery and reused, at least for four consecutive cycles, maintaining 83 % of the initial activity and concomitant rather high selectivity. 3-Amino-2-pyrazinecarboxylic acid is used to synthesize three new iron(III) complexes which act as heterogeneous catalysts for the solvent-free microwave-assisted peroxidative oxidation of 1-phenylethanol.